2022
DOI: 10.48550/arxiv.2204.08245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noether charge formalism for Weyl transverse gravity

Abstract: Weyl transverse gravity is a gravitational theory that is invariant under transverse diffeomorphisms and Weyl transformations. It is characterised by having the same classical solutions as general relativity while solving some of its issues with the cosmological constant. In this work, we first find the Noether currents and charges corresponding to local symmetries of Weyl transverse gravity as well as a prescription for the symplectic form. We then employ these results to derive the first law of black hole me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several years ago, in Ref. [2] it was pointed out that the Noether current associated with the Weyl symmetry in a Weyl invariant scalar-tensor gravity [3] vanishes identically by both a direct evaluation and the second Noether theorem [4,5], and afterwards it was shown that the same result holds for conformal gravity by dealing with it as a gauge natural theory [6], the unimodular gravity [7] and the Weyl transverse gravity [8,9] by a direct calculation.…”
Section: Introductionmentioning
confidence: 94%
“…Several years ago, in Ref. [2] it was pointed out that the Noether current associated with the Weyl symmetry in a Weyl invariant scalar-tensor gravity [3] vanishes identically by both a direct evaluation and the second Noether theorem [4,5], and afterwards it was shown that the same result holds for conformal gravity by dealing with it as a gauge natural theory [6], the unimodular gravity [7] and the Weyl transverse gravity [8,9] by a direct calculation.…”
Section: Introductionmentioning
confidence: 94%